Xylooligosaccharide supplementation decreases visceral fat accumulation and modulates cecum microbiome in mice. (January 2019) - Long, Jianfeng; Yang, Jieping; Henning, Susanne M.; Woo, Shih Lung; Hsu, Mark; Chan, Brenda; Heber, David; Li, Zhaoping
Graphical abstract: Highlights: Effects of dietary XOS in mice fed a low soluble fiber diet (LSFD). Dietary XOS induced changes of gut microbial composition. High dose XOS (7%) decreased the obese-related gut bacterial phenotype. High dose XOS (7%) decreased visceral fat depots. The formation of cecal SCFAs was not required for the effect of XOS on adiposity. Abstract: Xylooligosaccharide (XOS), an oligosaccharide with great prebiotic potential, has been shown to modulate the gut microbiota. Our aim was to determine the effects of dietary XOS supplementation on body composition, lipid metabolism and intestinal microbiota using a mouse model. Our data showed that XOS dietary supplementation at 2.1 and 7.0% significantly changed the gut microbial composition. A decrease in visceral fat depots, concentration of inflammatory cytokine MCP-1, and abundance of the two most important obesity associated gut microbial phyla Firmicutes and Bacteroidetes were observed with 7% XOS supplementation. No change in blood or liver lipids was observed with both XOS doses. The production of SCFAs in the cecum was increased and relative abundance of Actinobacteria was decreased with supplementation of both doses of XOS. To conclude, XOS supplementation reduced adiposity through decreasing gene expression of markers of adipogenesis and fat synthesis and induced changes in intestinal microbial composition.